2D Layered Bimetallic Phosphorous Trisulfides MIMIIIP2S6 (MI = Cu, Ag; MIII = Sc, V, Cr, In) for Electrochemical Energy Conversion. Issue 2 (5th January 2023) - Oliveira, Filipa M.; Paštika, Jan; Plutnarová, Iva; Mazánek, Vlastimil; Strutyński, Karol; Melle‐Franco, Manuel; Sofer, Zdeněk; Gusmão, Rui
Abstract: Considerable improvements in the electrocatalytic activity of 2D metal phosphorous trichalcogenides (M2 P2 X6 ) have been achieved for water electrolysis, mostly with M II 2 [P2 X6 ] 4− as catalysts for hydrogen evolution reaction (HER). Herein, M I M III P2 S6 (M I = Cu, Ag; M III = Sc, V, Cr, In) are synthesized and tested for the first time as electrocatalysts in alkaline media, towards oxygen reduction reaction (ORR) and HER. AgScP2 S6 follows a 4 e − pathway for the ORR at 0.74 V versus reversible hydrogen electrode; CuScP2 S6 is active for HER, exhibiting an overpotential of 407 mV and a Tafel slope of 90 mV dec −1 . Density functional theory models reveal that bulk AgScP2 S6 and CuScP2 S6 are both semiconductors with computed bandgaps of 2.42 and 2.23 eV, respectively and overall similar electronic properties. Besides composition, the largest difference in both materials is in their molecular structure, as Ag atoms sit at the midpoint of each layer alongside Sc atoms, while Cu atoms are raised to a similar height to S atoms, in the external segment of the 2D layers. This structural difference probably plays a fundamental role in the different catalytic performances of these materials. These findings show that M I (Cu, Ag) together with Sc(M III ) leads to promising achievements in M I M III P2 S6 materials as electrocatalysts. Abstract : 2D bimetallic phosphorous trisulfides M I M III P2 S6 (M I = Cu, Ag; M III = Sc, V, Cr, In) are tested for the first time as electrocatalysts in alkaline media. AgScP2 S6 exhibits a higher mass activity toward the oxygen reduction reaction. For the hydrogen evolution reaction, CuScP2 S6 shows an overpotential of 407 mV and a Tafel slope of 90 mV dec −1 .